Biofilm formation and antimicrobial resistance genes of coagulase-negative staphylococci isolated from cows with mastitis in Argentina. Issue 8 (13th January 2017) - Srednik, Mariela E.; Tremblay, Yannick D. N.; Labrie, Josée; Archambault, Marie; Jacques, Mario; Fernández Cirelli, Alicia; Gentilini, Elida R.
Abstract: Mastitis affects the health and welfare of dairy cows worldwide. Coagulase-negative staphylococci (CNS) are known to form biofilms and are increasingly recognized as a cause of persistent bovine intramammary infections. A total of 90 CNS isolated from cows with clinical and subclinical mastitis in Argentina from 2008 to 2014 were identified by PCR-RFLP using the gap gene. Standard microtiter plate assays were used to assess CNS biofilm formation, and Staphylococcus haemolyticus species formed the strongest biofilms. The presence of biofilm-associated genes ica A, bap and aap was detected in a few isolates, while emb P, fbe, atl E and eno were present in the majority of isolates. Genes encoding resistance to β-lactams were detected among the isolates; bla Z, mec A and mec C were detected in 21, 4 and 1 isolate, respectively. Resistance to macrolides and lincosamides ( n = 6) was attributable to erm B, erm C, mph C or mrs A or a combination of those genes. In this study, we identified CNS species involved in mastitis and provide information about pathogenicity and antimicrobial resistance, which is essential to design efficient strategies to control mastitis caused by CNS. Abstract : Biofilm formation, biofilm-associated genes and antimicrobial resistance genes of coagulase-negative staphylococci isolated from cows with mastitis in Argentina.